2016
DOI: 10.1038/srep23769
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the role of GGDEF-EAL domain proteins in virulence and motility in Xanthomonas oryzae pv. oryzicola

Abstract: The second messenger c-di-GMP is implicated in regulation of various aspects of the lifestyles and virulence of Gram-negative bacteria. Cyclic di-GMP is formed by diguanylate cyclases with a GGDEF domain and degraded by phosphodiesterases with either an EAL or HD-GYP domain. Proteins with tandem GGDEF-EAL domains occur in many bacteria, where they may be involved in c-di-GMP turnover or act as enzymatically-inactive c-di-GMP effectors. Here, we report a systematic study of the regulatory action of the eleven G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…oryzicola (Xoc) and Xoo. The effects of deletion/mutation of the genes encoding some of these proteins have been reported to effect virulence and biofilm formation (Wei et al 2016;Yang et al 2016;Su et al 2016b;Li et al 2018;Xue et al 2018). The majority of these proteins contain further domains that have a role in recognition of different environmental cues or comprise regulatory elements of two-component systems, such as the HD-GYP domain protein RpfG introduced above.…”
Section: Intracellular Signalling Mediated By Nucleotide Second Messementioning
confidence: 99%
“…oryzicola (Xoc) and Xoo. The effects of deletion/mutation of the genes encoding some of these proteins have been reported to effect virulence and biofilm formation (Wei et al 2016;Yang et al 2016;Su et al 2016b;Li et al 2018;Xue et al 2018). The majority of these proteins contain further domains that have a role in recognition of different environmental cues or comprise regulatory elements of two-component systems, such as the HD-GYP domain protein RpfG introduced above.…”
Section: Intracellular Signalling Mediated By Nucleotide Second Messementioning
confidence: 99%
“…GGDEF and EAL domains are often present in the same protein 14 . In these cases, proteins can either be bi-functional 15 or only one of the domains possesses catalytic activity 16 . Other proteins implicated in c-di-GMP related functions contain sensor or receptor domains, such as the PilZ domain 17 , among others.…”
Section: Introductionmentioning
confidence: 99%
“…As this paradigm was examined in a progressively larger number of bacteria, many microbes were found to contain a surprising number of DGCs and PDEs, numbering past 60 in some cases (23). Critically, despite the sheer number of DGCs at work, many studies have demonstrated that most DGCs appear to specifically signal for one or two c-di-GMP-dependent processes, indicating some kind of mechanism(s) that allows a given DGC to activate a specific effector (25, 43, 47, 66, 67). These observations gave rise to tension between the idea that effectors can sense the c-di-GMP signal from a specific DGC, and the idea that any one DGC is making the same small, diffusible molecule as its sibling enzymes in the open space of the bacterial cytoplasm.…”
Section: Introductionmentioning
confidence: 99%